B-cell activating factor as a serological biomarker for polymyositis and dermatomyositis. (March 2014) - Peng, Qing-Lin; Shu, Xiao-Ming; Wang, Dong-Xue; Wang, Yan; Lu, Xin; Wang, Guo-Chun
Aim: To investigate serum levels of B-cell activating factor (BAFF) in the patients with polymyositis (PM) and dermatomyositis (DM), and to systematically examine the association between serum BAFF levels and disease activity in PM/DM patients.Patients & methods: A cross-sectional analysis included 92 PM/DM patients and 25 healthy control subjects. A longitudinal study followed 24 patients. Serum BAFF concentrations were detected by the ELISA method.Results: Serum BAFF levels in PM/DM patients were significantly higher than those in healthy controls. A cross-sectional assessment revealed a modest correlation between serum BAFF levels and global disease activity and a mild correlation between serum BAFF levels and muscle disease activity. The longitudinal study showed that serum BAFF levels modestly correlated with global disease activity and muscle disease activity.Conclusion: Resulting data showed high serum BAFF levels in PM/DM patients and suggested BAFF as a serological biomarker for PM/DM disease activity.